Penerapan Aplikasi Trichoderma untuk Meningkatkan Produksi Cabai Bebas Residual Pestisida Kimia di Desa Wolasi, Kecamatan Wolasi, Kabupaten Konawe Selatan - HS, Gusnawaty; Muhammad Taufik; Muhammad Botek (Bengkulu Institute, 2025)
The aim of this community service activity is to empower chili farmers/groups to enhance chili production and produce healthy chili free from pesticide residues using local Trichoderma. The specific target is to improve the knowledge and skills of the partner farmer groups in using Trichoderma sp. and producing organic fertilizer based on local Trichoderma as a biopesticide and biofertilizer, enabling farmers to increase chili production while producing healthy, pesticide-free chili. The community service activities were conducted in Wolasi Village, Wolasi District, South Konawe Regency. The method used was training with demonstrations on plots (demplot). The stages of the activities included: socialization, training on making organic fertilizer based on Trichoderma sp., training on Trichoderma sp. propagation using bran media, and the creation of a demplot for Trichoderma application as a biopesticide and biofertilizer. The expected outcomes include farmers understanding the negative impact of excessive and improper use of chemical pesticides on the environment and chili products, as well as learning safe farming practices using microorganisms like Trichoderma sp.. Farmers will also gain knowledge on the role of Trichoderma sp. in enhancing production, promoting plant growth, and improving plant resistance, along with acquiring skills in propagating and applying Trichoderma sp. and producing organic fertilizer based on Trichoderma sp. for use as a biopesticide and biofertilizer.